Analysis Of Facebook Company - Wang, Chenyu (International Journal of Global Economics and Management, 2024)
As a leader in the global technology industry and one of the largest listed companies, Facebook takes selling advertising space as its core business and is committed to maintaining sufficient innovation and competitiveness in business and products. Even so, revelations of privacy breaches, misinformation, and anti-competitive practices have made investors more cautious about the company’s investment decisions. From a portfolio and capital management perspective, diversifying the portfolio and reducing the correlation between assets helps Facebook deliver attractive expected returns. In terms of net present value, Facebook’s cash flow sources and capital allocation priorities should reflect the company’s ability to buy back shares and capital expenditures. Through a critical analysis and discussion of Facebook, the paper measures whether Facebook’s business model has the ability to expand rapidly, increase stock value and market valuation, and attract more investment from the management and financial perspectives of the company’s management structure, capital composition, and net present value of the company’s assets.